Preparation and Evaluation of Noodles From Some Legumes Powder - Wael, M. Mospah; Elshahat, G. El-Dreny; Gamal, S. El-Hadidy (Food Technology Research Journal)
Instant noodles, renowned for their affordability, convenience, and diverse flavors, represent a popular global cereal product. This study explored the potential of incorporating unconventional ingredients, specifically lentil, pea, and bean powders, to enhance the nutritional profile and sensory attributes of instant noodles. The objective was to investigate the feasibility of coloring wheat flour-based instant noodles using these legume powders while assessing their impact on chemical composition, color characteristics, and overall acceptability. Instant noodles were fortified with 15-30% red lentil powder (RLP), green pea powder (GPP), red kidney bean powder (RKBP), or a combination thereof, employing lamination technology. The incorporation of kidney bean powder significantly elevated dietary fiber, ash, protein, and essential amino acid content, including lysine. Total essential amino acid content increased from 33.35% to 37.75% with a 30% RLP replacement and to 36.22% with a 30% mixed legume powder replacement. Legume flour addition imparted distinct color variations to the noodles, with red lentil powder proving most effective as a natural colorant. Sensory evaluation revealed that noodles enriched with 30% red lentil powder garnered the highest consumer preference and exhibited the most intense color.